Monitoring FTD in the peripheral blood mononuclear cells of elderly patients with metastatic colorectal cancer administered FTD plus bevacizumab as first‐line treatment. Issue 6 (3rd May 2021) - Fujimoto, Yoshiaki; Oki, Eiji; Qiu, Shichao; Nakanishi, Ryota; Makiyama, Akitaka; Miyamoto, Yuji; Kotaka, Masahito; Shimokawa, Mototsugu; Ando, Koji; Kimura, Yasue; Kitao, Hiroyuki; Maehara, Yoshihiko; et al.
Abstract: Trifluridine/tipiracil (FTD/TPI) is an orally administrated anticancer drug with efficacy validated for patients with metastatic colorectal cancer (mCRC) or gastric cancer. FTD, a key component of FTD/TPI, exerts antitumor effects via its incorporation into DNA. Using specific antibodies against bromodeoxyuridine, FTD incorporation into DNA is detected in tumors and peripheral blood mononuclear cells (PBMC) of patients with mCRC who are administered FTD/TPI. The proportion of FTD‐positive PBMC fluctuates according to the schedule of treatment, although the association between the proportion of FTD‐positive PBMC and the clinical outcomes of patients is unknown. To answer this question, here we monitored the FTD‐positive PBMC of 39 elderly patients with mCRC enrolled in KSCC1602, a single‐arm phase 2 trial of FTD/TPI plus bevacizumab as a first‐line treatment, for 1 month, during the first cycle of treatment. The median values and interquartile ranges of the percentage of FTD‐positive PBMC on days 8, 15, and 29 were 39.3% (30.7%‐52.2%), 66.9% (40.0%‐75.3%), and 13.5% (5.7%‐26.0%), respectively. Receiver operating characteristic analysis revealed that the percentage of FTD‐positive PBMC on day 8 (the end of the first week of treatment) had moderate ability to accurately diagnose the occurrence of severe neutropenia and leukopenia within 1 month (area under the curve = 0.778 [95% confidence interval, 0.554‐0.993]). This result suggests that excess FTD incorporation into PBMC at the initial phase of FTD/TPI plus bevacizumab treatment is a risk factor for early onset of severe hematological adverse events. Abstract : Severe hematological adverse events were predicted by FTD incorporation into PBMC during the early phase of FTD/TPI plus bevacizumab treatment. However, FTD‐positive PBMC were not associated with prognosis.